The Impact of Personality Traits on Gen Z’s Intentions to Buy Eco-Friendly Products in Surakarta - Ilyas Alfida' Abdillah; Rini Kuswati (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study explores the factors influencing the purchase intention of environmentally friendly products among Generation Z in Surakarta, Indonesia. Utilizing the Theory of Planned Behavior framework, the research examines the roles of environmental attitudes, environmental awareness, trust, and green self-identity in shaping purchase intentions. Data were collected from 384 respondents via an online survey and analyzed using SmartPLS. The findings reveal that positive attitudes, awareness, and trust in environmentally friendly products significantly affect purchase intentions. However, green self-identity does not exhibit a significant impact. These results underscore the importance of educational campaigns that foster positive attitudes and consumer trust in sustainability claims. The study contributes to consumer behavior literature and provides strategic insights for businesses to address the growing environmentally conscious market. Future research is recommended to incorporate additional variables, expand geographic coverage, and employ qualitative approaches to gain a deeper understanding of purchase behavior dynamics.